PENGEMBANGAN PRODUK BERBASIS MAHKOTA DEWA (Phaleria macrocarpa) SEBAGAI MINUMAN FUNGSIONAL UNTUK MEMPERTAHANKAN LOYALITAS KONSUMEN - , ANJAR KISTIA PURWADITYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Crown of god used by many Indonesian people as functional drinks such as crown of god tea from PT Salama Nusantara, because it has many properties. One of the properties of the crown of god was capable to lowering blood sugar levels of saponins effect of crownof god. But the crown of god has a disadvantge that costumers complain a lot, the bitter taste. Many Indonesian people consume crown of god with caloric sweeteners addition to reduce the bitter taste (product on the market have not been sweetened). Choice of sweeteners addition will be better if itâs a non-caloric one, such as stevia that has a high level of sweetness. According to quality attributes based on customer needs and properties of both material, a combination of them has potency to be developed into functional drinks as an effort to maintain costumersâ loyalty. This research used value engineering method that first begun with phase information, identification of customer needs carried at this phase. Second, analysis phase, this phase was conducted to determine the factors that influence the concepts product development using FAST diagrams (Function Analysis System Technique). Third, phase of creativity, to determine the specifications for developing concept alternative product. Fourth, phase determination, started with the sensory test continued with determining the performance and value of each product. Two products with the highest value would be tested financial and market validation followed by selling products directly to consumers to determine consumers' willingness to buy products developed. The result of this research on quality attributes product of Stevia Dewa, from the highest to lowest interest rate, according to the consumer is flavor, raw materials, price, shape, and durability. Two product concept with the highest value is concept D and F were made from the crown of the gods and stevia in sequence composition ratio is 1:1 and 1:3. Market validationâs result showed the highest sales market is product concept D (44.5%) higher than product concept F (22.2%) and product markets (33.3%).